Eksplorasi Perilaku Bullying Di Pesantren - Zidni Nuris Yuhbaba (Jurnal Kesehatan dr. Soebandi, 2019)
Bullying behavior is often the case among teenagers nowadays, not only in the school environment but also in the islamic boarding school which is where the education of religious. The impact of bullying can interfere with adolescent mental health, especially for its victims.The impact among them is fear, feeling ashamed, depressed, sad and anxious.Physical impact is also felt by victims of bullying, such as swelling, injury, sleeplessness, decreased appetite.The research is a bertujun to explore the experiences of bullying. Explore students ' understanding of bullying, the form of bullying experienced, causes, perpetrators and perceived consequences.The design of the study used is qualitative with interpretive phenomenological approaches.Research was conducted in one of the islamic boarding school in Jember. Data retrieval using in-depth interview techniques for 30-60 minutes using a recording device. Five participants chosen by purposive sampling method with criteria are students who have experienced bullying, stay in islamic boarding school at least 1 year, able to tell the experience and be willing to become participants.The results of research show that participants understand bullying as violence, the form of bullying that is experienced in the form of physical bullying, verbal bullying and social bullying.Perpetrators are senior as well as peers, due to competition, desire to be recognized, fad and lack of concern from the islamic boarding school. He perceived impact of participants in the form of physical harm, feeling uncomfortable, sad, frightened, anxious to want to stop or leave from the pesantren.The case of bullying occurring in the boarding school environment resulted in a bad impact on the victims in the bio-psycho-and social development of the victim.The islamic boarding school and parents need to give special attention to the students, and give a deeper understanding of how to cope with bullying in pesantren.